مركز مجلس الأمة الجزائري على ضوء التعدیل الدستوري الأحدث - بدر الدين مهري; خير الدين موله (My University, 2017)
Summary: What distinguishes this study as an update, based on Constitutional Amendment 16-01 as well as the amendment of Organic Law 99-02 by Organic Law 16-12 regulating the relationship and staffing relationship between the National People's Assembly and the Council of the Nation and the Government; Despite the novelty of the National Assembly in the Algerian parliamentary system, it has gone a long way in the Parliament's place, especially in the face of executive power. And indeed, this study has allowed us to Algeria, which has been able to establish itself as an irreplaceable Bikamerale system. By examining and scrutinizing the weight and constitutional and legal value of the National Assembly as the second chamber of Parliament, our study confirms that the formation of the Council of the Nation is a preconceived idea created by the comparative systems from the English system to the American system French, and then the systems circulated until most of the world's countries had two-chamber parliaments. And, as we have stated, Algeria, because of the political and legal reasons it has experienced, has introduced this bilateral system of Parliament, We have also touched upon the composition of the National Assembly, which is based on combining the method of election and appointment to avoid the shortfall caused by the electoral representation. Since the National Assembly is a constitutional institution, the latter enjoys administrative structures that have its role and standing in the Chamber. Administrative regulation is not sufficient for the survival of any institution alone. The Council has promoted a financial aspect that is independent from the preparation, operation and disbursement. ............................. الملخص : ما یمیز هذه الدراسة أنها حدیثة، انطلاقا من التعدیل الدستوري 16-01 وكذا تعدیل القانون العضوي 99-02 بالقانون العضوي 16-12 المنظم لعلاقة المجلس الشعبي الوطني ومجلس الأمة والعلاقة الوظیفیة بینهما وبین الحكومة، و على الرغم من حداثة مجلس الأمة في النظام البرلماني الجزائري إلا أنه قطع شوطا لا یستهان به في مكانة البرلمان خاصة في مواجهة السلطة التنفیذیة، والواقع أن هذه الدراسة قد سمحت لنا الجزائري التي إستطاعت أن ترسخ نفسها كنظام بیكامیرالي لا یمكن الاستغناء عنه. بالبحث والتدقیق في الوزن والقیمة الدستوریة والقانونیة لمجلس الأمة كغرفة ثانیة للبرلمان وتؤكد دراستنـــا أن نشأة مجلس الأمــــة هي فكرة قدیمة أوجدتهــــا الأنظمة المقـــــارنة بدایــة من النظام الإنجلیزي إلى النظام الأمریكي، فالفرنسي، ثم تداولته النظم إلـى أن أصبحت أغلب دول العالم تتشكل برلماناتها من غرفتین، وكما ذكرنا فالجزائر و نظرا للأسباب السیـــاسیة والقــــانونیة التي عـــایشتها فقد أخذت بهذا النظــام الثنائي للبرلمــان، كما تطرقنـا إلى أن تشكیلة مجلس الأمة التي تقوم على الجمع بین أسلوب الانتخاب والتعیین لتفادي النقص الحاصل من جراء ما ینجم عن التمثیل الانتخابي، وعلى اعتبار أن مجلس الأمة مؤسسة دستوریة فإن هذه الأخیر ة تتمتع بهیاكل إداریة لها دورها ومكانتها داخل الغرفة وكما أن التنظیم الإداري غیر كافي لوحده لبقاء أي مؤسسة فقد حضي المجلس بجانب مالي یتمیز بالإستقلالیة من حیث الإعداد والتسییر والصرف . .............................. Résumé : Ce qui distingue cette étude en tant que mise à jour, basée sur l’amendement constitutionnel 16-01 ainsi que la modification de la loi organique 99-02 par la loi organique 16-12 réglementant les relations et le rapport de dotation entre l’Assemblée nationale du peuple et le Conseil de la nation et le gouvernement ; Malgré la nouveauté de l’Assemblée nationale dans le système parlementaire algérien, Il a fait beaucoup de chemin à la place du Parlement, surtout face au pouvoir exécutif. Et en effet, cette étude nous a permis de nous rendre en Algérie, qui a su s’établir comme un système irremplaçable de Bikamerale. En examinant et en scrutant le poids, la valeur constitutionnelle et juridique de l’Assemblée nationale en tant que deuxième chambre du Parlement, notre étude confirme que la formation du Conseil de la Nation est une idée préconçue créée par les systèmes comparatifs du système anglais au système américain français, et puis les systèmes circulant jusqu’à ce que la plupart des pays du monde aient des parlements bicaméraux. Et comme nous l’avons dit, l’Algérie, pour des raisons politiques et juridiques qu’elle a vécues, a introduit ce système bilatéral de parlement, Nous avons également abordé la composition de l’Assemblée nationale, qui est basé sur la combinaison de la méthode d’élection et de nomination pour éviter le déficit causé par la représentation électorale. Étant donné que l’Assemblée nationale est une institution constitutionnelle, cette dernière bénéficie de structures administratives qui ont leur rôle et leur statut à la Chambre. La réglementation administrative ne suffit pas à elle seule pour assurer la survie d’une institution. Le Conseil a promu un aspect financier indépendant de la préparation, du fonctionnement et des décaissements.